Zagadnienie podwyższenia efektywności nauczania języków obcych i wybrane aspekty socjalnej teorii lingwodydaktycznej - Siatkowski, Stanisław (Studia Rossica Posnaniensia, 2017)
The article opens with a discussion of the main educational and organizational reasons, as well as other circumstances (for example, the lack of publicly entitled language policy in the country) for the relatively low effectiveness of recent teaching of foreign languages, in particular Russian language, in comparison to some highly developed countries in Western Europe. The author goes on to introduce the significant current substantive (scientific) issues of the new approach to a practically oriented theory of teaching foreign languages — social glottodidactics.